ENGLISH LESSONS FOR PRIMARY CLASSES ARE INTERESTING AND EFFECTIVE ORGANIZATION - Boqiyeva Marjona Shuhratovna (Лучшие интеллектуальные исследования, 2023)
Abstract: In this article, modern teaching of English in primary grades approaches and innovations as a result of the use of methods, of students development of logical thinking skills, fluency of speech, quick and correct answer formation of teaching skills, enthusiasm for knowledge, thorough preparation for classes information about what they want to see.